(untitled) (La Lupa. Colección fueguina de divulgación científica, 2025)
COMITÉ EDITORIAL Editora responsable María Paz Martinoli Editores asistentes Jimena Elizabeth Chaves Damián A. Fernández Mauricio González Guillot Cecilia Inés Gutiérrez María Constanza Maluendez Testoni Victoria Mosqueira González Paula Rodríguez Fernando C. Santiago Asesores informáticos Fernando Gini Rodrigo Leandro Gauna Colaboradores Julia Tilton Henry Hodde Facundo Sota Diseño y Diagramación Irina Castro Peña Ushuaia, Tierra del Fuego, Argentina Instagram: @disenioalsur Impresión M&A Diseño y Comunicación S.R.L. Buenos Aires, Argentina E-mail: info@myaweb.com.ar